ZmpTAC12 binds single‐stranded nucleic acids and is essential for accumulation of the plastid‐encoded polymerase complex in maize. Issue 3 (19th January 2015) - Pfalz, Jeannette; Holtzegel, Ute; Barkan, Alice; Weisheit, Wolfram; Mittag, Maria; Pfannschmidt, Thomas
Summary: The plastid‐encoded plastid RNA polymerase (PEP) represents the major transcription machinery in mature chloroplasts. Proteomic studies identified four plastome‐ and at least ten nuclear‐encoded proteins making up this multimeric enzyme. Depletion of single subunits is known to result in strongly diminished PEP activity causing severe defects in chloroplast biogenesis. Here, we characterized one PEP subunit in maize, ZmpTAC12, and investigated the molecular basis underlying PEP‐deficiency in Zmptac12 mutants. We show that the ZmpTAC12 gene encodes two different protein isoforms, both of which localize dually in chloroplasts and nuclei. Moreover, both variants assemble into the PEP‐complex. Analysis of PEP‐complex assembly in various maize mutants lacking different PEP‐complex components demonstrates that ZmpTAC12, ZmpTAC2, ZmpTAC10 and ZmMurE are each required to accumulate a fully assembled PEP‐complex. Antibodies to ZmpTAC12 coimmunoprecipitate a subset of plastid RNAs that are synthesized by PEP‐dependent transcription. Gel mobility shift analyses with recombinant ZmpTAC12 revealed binding capabilities with ssRNA and ssDNA, but not dsDNA. Collectively these data demonstrate that ZmpTAC12 is required for the proper build‐up of the PEP‐complex and that it interacts with single‐stranded nucleic acids. Abstract : See also the Commentary by Peter Kindgren and Åsa Strand